2021
DOI: 10.1093/ecco-jcc/jjab216
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Ulcerative Colitis Is a Fibrotic Disease and Is Linked with Chronicity of Inflammation

Abstract: Background & Aims Intestinal fibrosis has recently been characterized in adult ulcerative colitis and may affect motility, diarrhea, and the symptom of urgency. We aimed to characterize the presence of fibrosis in pediatric patients with ulcerative colitis, and its link to severity and chronicity of mucosal inflammation, as well as clinical factors of severity. Methods We performed a single center cross-sectional study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Yet, as our understanding of involvement beyond the mucosa in UC evolves, the importance of achieving transmural healing in UC may become clearer. 9 The current study by Allocca et al sheds light on this, 3 and provides the first evidence of the utility of a validated transmural ultrasound score to predict disease progression in UC. The key findings of this study are the ability of a MUC score >6.2 to predict a negative disease course (Hazard Ratio [HR] 3.87, 95% confidence interval [CI] 2.25-6.64).…”
Section: Ulcerative Colitis a Transmural Disease Requiring An Accurat...mentioning
confidence: 64%
See 1 more Smart Citation
“…Yet, as our understanding of involvement beyond the mucosa in UC evolves, the importance of achieving transmural healing in UC may become clearer. 9 The current study by Allocca et al sheds light on this, 3 and provides the first evidence of the utility of a validated transmural ultrasound score to predict disease progression in UC. The key findings of this study are the ability of a MUC score >6.2 to predict a negative disease course (Hazard Ratio [HR] 3.87, 95% confidence interval [CI] 2.25-6.64).…”
Section: Ulcerative Colitis a Transmural Disease Requiring An Accurat...mentioning
confidence: 64%
“…Achievement of deep remission using this treat‐to‐target approach in Crohn's disease has shown to prevent disease progression in a post‐hoc analysis of the CALM trial, 8 but this has not yet been shown prospectively in UC. Yet, as our understanding of involvement beyond the mucosa in UC evolves, the importance of achieving transmural healing in UC may become clearer 9 . The current study by Allocca et al.…”
mentioning
confidence: 69%
“…Inflammatory bowel disease is a chronic, recurrent, and autoimmune disease that primarily occurs in the colon and bowel and includes Crohn's disease and ulcerative colitis (UC) [ 1 , 2 ]. UC is a common diffuse, nonspecific, and recurrent inflammatory disease of the rectum and colon mucosa and submucosa with high rates of relapse and canceration [ 3 ]. The incidence of UC has recently increased [ 4 ] with over 6.8 million cases having been reported worldwide [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of UC has recently increased [ 4 ] with over 6.8 million cases having been reported worldwide [ 5 ]. Moreover, the age of onset tends to be 20–40 years old and can also be seen in children or the elderly [ 3 ]. It can be characterized by periods of remission followed by repeated flare-ups [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation